The Intention to Use Smart Home Internet of Things (IoT) among Generation Y : An Application of The Technology Acceptance Model (TAM) - Yap, Zi Yuan; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2023)
Internet of Things (IoT) technology is having an expanding influence on our everyday lives as a result of recent advancements in internet technologies, and it is beginning to offer intriguing and beneficial new services. Due to IoT growth is still in its early stages, comprehending the problem from the standpoint of individual customers has received little attention. This research seeks to evaluate a technology acceptance model of variables impacting consumer adoption of IoT technology, given the significance of the new technology and the difficulties of comprehending the customer. The research aims to apply Technology Acceptance Model (TAM) in determining intention to use Smart Home IoT technology. Based on Technology Acceptance Model (TAM), the authors proposed an IoT acceptance model that consists of two variables that are perceived usefulness and perceived ease of use. The respondents of this research will involve among the Generation Y in Johor. The research will adapt quantitative research method whereby survey questionnaire be used as data collection tool. The response rate was 75.52% which was 290 out of 384 and all of the questionnaires collected were usable. Data have been analyzed by using SPSS (Statistic Package for Social Sciences) statistical software. The resulted of this research shows level of intention to use Internet of Things (IoT) had high mean score which is 4.16, perceived usefulness with Intention to use Internet of Things (IoT) had high mean score which is 4.27 and perceived ease of use with intention to use Internet of Things (IoT) had high mean score which is 4.28.